FORMATION OF LAYERS BY PLASMA NITRIDING IMPOSED TO 32CrMoV13 LOW ALLOY STEEL FORMATION DES COUCHES PAR NITRURATION PLASMA IMPOSEE A L’ACIER FAIBLEMENT ALLIE 32CrMoV13 - CHALA, A.; SAIED, C.; BOUMERZOUG, Z.; CHEKOUR, L.; S. AIDA, M. (Courrier du Savoir, 2014)
The aim of the study is to optimise the application of heat treatments by modifying the nitriding conditions in high temperature process. The influence of gas mixture (composed of N2, H2 and CH4) and time of nitriding on the mechanical and structural properties of 32CrMoV13 low alloy steel samples was studied. The composition and structure of the nitrided layers was determined by EDS and XRD respectively. Vickers micro hardness profiles were also performed to study the influence of the gas mixture and time of nitriding. The morphology of the nitrided layers was observed by optical microscopy. EDS analyses permitted to verify the composition of the layers while their structure was determined by XRD. The time of nitriding was influent on the diffusion layer’s thickness and properties. Furthermore, it was obvious that increasing the nitrogen contents from 20 to 80 % in the nitriding gas mixture N2+H2 or adding 5% of methane permits to increase the nitrided layer’s thickness and hardness. The duplex treated samples obtained with 80 % of N2 or 5% CH4 performed best and allowed to increase almost twice the tools service life.   Le but de ce papier est d’optimiser le traitement thermique de nitruration ionique par plasma et ce en modifiant les conditions de nitruration à haute température. L’influence du mélange gazeux (composé de N2, H2 et CH4) et le temps de nitruration sur les propriétés mécaniques et structurales de l’acier faiblement allié 32CrMoV13 a été étudié. La composition et la structure des couches de nitruration ont été déterminées par microanalyse EDS et diffraction des rayons X respectivement. Des profiles de microdureté Vickers ont été réalisés afin de voir l’effet du mélange gazeux et du temps de nitruration. La morphologie des couches a été observée par microscopie optique. Le temps de nitruration influe directement sur l’épaisseur et les propriétés des couches blanches et de diffusion. Il est évident que l’augmentation du pourcentage d’azote de 20 à 80 % dans le mélange gazeux (N2+H2) ou l’addition de 5 % de méthane (CH4) conduit à une augmentation remarquable de la dureté et des épaisseurs des couches.